A teoria normativa da democracia de Norberto Bobbio - Andrighetti, Leandro (2009)
This thesis aims at clarifying what democracy is. Is it a form of government that establishes who rules (one, a few, or many) or is it a form of government that determines how it can be ruled (in a despotic and autocratic way or in a democratic manner)? The hypothesis is that in more complex societies, democracy is defined as the fundamental values and rules that establish who is authorized to make collective decisions following determined procedures. That democracy offers conditions towards the accomplishment of fundamental principles such as equality and political freedom, both from the perspective of individuals as well as from the society. Such principles, in their turn, are judicially and politically guaranteed, by a set of rules capable of ensuring them. The objective of this research is to examine the arguments that Norbert Bobbio holds concerning what democracy is. To do so, the social sciences approach is distinguished from the philosophical approach in the analysis of democracy; the justifications of the democratic State are analysed; and the ancient and modern democracy, as well as the democratic rules and procedures are defined; The investigation is carried out through bibliographical research of the main political works by Bobbio, such as: Equality and liberty; Liberalism and Democracy; The Future of Democracy: a Defense of the Rules of the Game; The Age of Rights; General Theory of Politics; Which Socialism?; Dictionary of Politics (co-authorship). In those works, Bobbio discusses the problem of democracy and highlights that political science approaches the issue of democracy from a different perspective from that of political philosophy. The former considers democracy as it is, and the latter how it should be. It considers as the main justifications of the democratic State, the freedom and equality of individuals. Does it define that the main problem of democracy, nowadays, is how it rules, or in other words, how it exercises power? For, a monarchic government can rule democratically whereas a democratic one can rule despotically. It is not the number of people that rule that defines if a regime is democratic or not, but how it exercises power. For power to be exercised democratically, it is necessary a set of fundamental rules that establish who is authorised to make decisions and with what procedures. From those conclusions, it can be observed that democracy in Bobbio takes an essentially ethical character inasmuch as he presupposes fundamental values such as political equality and freedom. The guarantee of those values is basic conditions for the development of individuals and society.